Women’s Perceptions and Roles in Environmental Preservation: A Phenomenological Study in Cirebon-Indonesia - Sunoto, Sunoto; Pudji Astuti, Tri Marhaeni; Lestari, Puji (Ilmu Inovasi Nusantara, 2024)
This study explores the perceptions of the community, with a specific focus on women, regarding their roles in environmental preservation in Cikeduk Village-Cirebon. The research employs a qualitative methodology, utilizing a phenomenological approach to delve deeply into the lived experiences and perceptions of women in this context. Data were collected through a combination of interviews, documentation, and direct observations within the village. To ensure the validity of the findings, the study implemented source and technique triangulation, while data analysis was conducted using the Miles, Huberman, and Saldana model, which includes data condensation, data display, and conclusion drawing. The study's findings revealed a dichotomy in perceptions concerning women's roles in environmental preservation. On one hand, positive perceptions highlight the belief that maintaining sanitation and greenery is not only a significant responsibility for ensuring community well-being and comfort but also provides economic benefits, particularly through activities like tree planting. On the other hand, negative perceptions are characterized by the belief that cleanliness is not a personal responsibility and is not a priority for many individuals. The study identified three key roles that women play in environmental management in Cikeduk: environmental education, reforestation efforts, and the management of domestic waste. These roles are crucial in shaping the village's approach to sustainability. Based on these findings, the study recommends enhancing environmental education from an early age to foster an environmentally conscious generation. It also suggests expanding women’s empowerment programs, particularly in environmental management, and addressing negative perceptions through targeted socialization efforts. These recommendations align with the ecofeminist perspective, which emphasizes the critical role of women as agents of change in environmental preservation